Analisis Waktu Tunggu Pelayanan Resep Rawat Jalan di RSJD Dr. Arif Zainudin Surakarta - Ricard Nixon Holo; Reni Ariastuti; Khotimatul Khusna (Yayasan Literasi Sains Indonesia, 2023)
Pharmaceutical service is a direct and responsible service to patients related to pharmaceutical preparations. Waiting time is one of the minimum service standards in the pharmacy sector in hospitals. The minimum standard of waiting time set by the Ministry of Health is 30 minutes for non-combined prescriptions and 60 minutes for compound prescriptions. This study aims to determine the average waiting time for outpatient prescription services for both finished and concoction drugs at RSJD dr. Arif Zainudin Surakarta compared to the Hospital Pharmacy Minimum Service Standards. This research was conducted with a descriptive cross-sectional method. Primary data was collected through direct observation and recording of waiting times prescription services in July 2022. The data were taken as many as 100 outpatient prescriptions consisting of 25 concoctions and 75 non-concoctions. The research data was processed using Microsoft Excel. In this study, the average waiting time for non-concoction prescription services was 24,7 minutes and for concoction recipes 41,08 minutes. Based on the results of the study, it was found that the average waiting time for prescription services at the Regional Mental Hospital dr. Arif Zainudin Surakarta has met the requirements according to the minimum service standards in hospitals is 30 minutes for non-combined prescriptions and 60 minutes for compound prescriptions